Mandibular glands in reproductives of asian termite coptotermes gestroi (Isoptera: Rhinotermitidae) - Costa-Leonardo, A. M. [UNESP]; Goncalves, F. C. [UNESP]; Laranjo, L. T. [UNESP] (Comite Interamericano Soc Microscopia Electronica-ciasem, 2009)
This study reports on the morphology of the mandibular glands in reproductives of Coptotermes gestroi, including foraging nymphs and queens of different ages. These exocrine glands are very small and located between the mandibles and maxillae. The mandibular glands are composed of two types of cells: class 3 secretory cells and small canal cells and are characterized by the presence of the end apparatus that is a structure responsible for the junction between the secretory cell and its canal cell. The end apparatus is formed by the receiving canal that has an inner interrupted cuticle and is surrounded by microvilli. The variation in the histology of these glands among the different reproductives was associated with the presence of extracellular spaces which function as secretion reservoirs. Older primary reproductives showed more dilated extracellular spaces inside of the glands in relation to younger and alate reproductives. The ultrastructure of secretory cells showed different types of secretion. Electron-lucid secretions were present in female alates (virgin queens) and small lipid droplets and large myeloid granules in 3-year-old queens. The enlarged extracellular spaces present in the histological sections of class 3 cells correspond to the reservoirs or regions full of secretion observed in the cell ultrastructure. The occurrence of different types of secretions in the mandibular glands among female reproductives of C. gestroi is in accordance with distinct glandular functions in different phases of the life of these individuals.
Keywords: Subterranean termite; mandibular glands; termite queens; Coptotermes gestroi